KESESUAIAN DAN DAYA DUKUNG KAWASAN PANTAI KUAKO SOAHUKU, KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Yandri Lewaney; Henderina Lelloltery; Billy B. Seipalla (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Coastal areas are transition zones between land and sea that have strong potential to be developed as tourism destinations due to their natural beauty and diverse attractions. One of these potential areas is Kuako Beach, located in Soahuku Village, Amahai District, Central Maluku Regency. This study aims to (1) assess the suitability level of Kuako Beach for coastal tourism activities, and (2) analyze the physical carrying capacity of the area for tourism purposes. Data collection was conducted through field observation, interviews, questionnaires, and direct measurements at the study site. The data were analyzed using descriptive analysis. The sampling technique used was accidental sampling, involving 50 respondents consisting of site managers and tourists. The type of data used in this study is primary data. The results show that Kuako Beach is classified as highly suitable, with a Tourism Suitability Index (TSI) value of 89.29%. Meanwhile, the carrying capacity of the area allows up to 349 people per day for swimming activities and 656 people per day for leisure activities.